Effect of different impregnated gutta-percha points on post operative discomfort (Mustansiria Dental Journal, 2018)
The purpose of this study was to compare levels of post operative discomfort after cleaning and shaping of root canals using intracanal medicaments. Two hundreds forty teeth requiring root canal treatment were included. At random, canals were cleaned and shaped with crown-down technique and then dried and one of the following medicaments was used. Group I: medicated with chlorhexidine containing gutta-percha points (Activ points). Group II: medicated with calcium hydroxide containing gutta-percha points and finally group III: with no medicaments. Access cavities were closed with a sterile cotton pellet and cavit. The patients recorded degree of discomfort of various time intervals after cleaning and shaping on a visual analogue scale for 72hr. A significant statistical difference was found in the degree of discomfort between the three groups.